Estabelecimento de ciclo de cura de pré-impregnados aeronáuticos - Costa, Michelle L.; Rezende, Mirabel C.; Botelho, Edson C. [UNESP] (Associação Brasileira de Polímeros, 2005)
Autoclave molding produces polymer composites, where the processing conditions can be optimized with physicochemical knowledge of the polymeric matrix. The cure reaction evolves simultaneously with changes in rheology, which is normally refered to as rheo-kinetic behavior. With the knowledge of the appropriate cure cycle one can identify the steps in which pressure should be applied and when to raise the temperature. This paper is aimed at investigating the cure, kinetics and rheological parameters of three prepreg epoxy systems, namely F161, F584 and 8552, which are currently used in the Brazilian aeronautic industry. Differential scanning calorimetry (DSC) and rheological techniques have been used, both in the isothermal and dynamic modes. Kinetics data were obtained from dynamic and isothermal DSC, with rheological measurements being carried out during the cure. The mathematical models used were the nth order reaction model and the autocatalytic model with order of 2. The gel temperature was ~100 °C, and the corresponding gelification time was 135 s. With the determination of the kinetics for the cure and of the rheological parameters of the prepreg systems, a cure cycle should be established that led to high-performance composites using the autoclave molding.

Os compósitos poliméricos podem ser produzidos via moldagem em autoclave, onde as condições de processamento podem ser otimizadas a partir do conhecimento físico-químico da matriz polimérica. A evolução da cinética da reação de cura ocorre simultaneamente com as modificações no comportamento reológico do sistema polimérico, sendo comum denominar o fenômeno de comportamento reo-cinético. O presente trabalho tem como objetivo conhecer os parâmetros de cura, cinéticos e reológicos, de três diferentes sistemas de pré-impregnados de resina epóxi (cura a 177 °C), conhecidos como F161, F584 e 8552, hoje usados na indústria aeronáutica brasileira. Este estudo foi realizado com o auxílio das técnicas de DSC e reologia, utilizando-se análises dinâmicas e isotérmicas. Com isso, foi possível estabelecer a ordem de reação e a cinética de cura dos sistemas estudados. Neste estudo, foram utilizados como modelos matemáticos o de ordem n e o autocatalítico com ordem total de aproximadamente 2. A temperatura de gel foi de ~100 °C, e o tempo de gel correspondente foi de 135 segundos. A partir do conhecimento da cinética de cura e dos parâmetros reológicos dos sistemas de pré-impregnados foi possível estabelecer um ciclo de cura destinado à consolidação das peças aeronáuticas via moldagem em autoclave.
Establishment of cure cycle of aeronautic prepregs
Keywords: Cure cycle; prepreg; cure kinetics; thermal and rheological analyses; Ciclo de cura; pré-impregnado; cinética de cura; análises térmicas e reológicas